Sofrimento psicológico relacionado à cessação do tabagismo em pacientes com infarto agudo do miocárdio - Moreira-Santos, Thyego Mychell [UNESP]; Godoy, Irma [UNESP]; de Godoy, Ilda [UNESP] (FapUNIFESP (SciELO), 2016)
Among all causes of preventable deaths, smoking is responsible for the greatest number of deaths worldwide and predisposes to fatal, noncommunicable diseases, especially cardiovascular diseases. Lifestyle changes are effective in the treatment of patients with smoking-related diseases and assist in the prevention of premature mortality. Our objective was to investigate the available scientific evidence regarding the psychological distress related to smoking cessation in patients who have had acute myocardial infarction. To that end, we conducted an integrative review of the literature in order to summarize relevant studies on this topic. The selected databases were Scopus, PubMed Central, Institute for Scientific Information Web of Science (Core Collection), ScienceDirect, EMBASE, SciELO, LILACS e PsycINFO. On the basis of the inclusion and exclusion criteria adopted for this study, 14 articles were selected for analysis. Those studies showed that the prevalence of psychological distress is higher among smokers than among nonsmokers, and distress-related symptoms are much more common in smokers with acute myocardial infarction than in those without. Smoking cessation depends on the active participation of the smoker, whose major motivation is the underlying disease. Most studies have shown that there is a need to create treatment subgroups as a means of improving the treatment provided. This review article expands the knowledge regarding smoking cessation and shows the need to invest in future research that investigates subgroups of smokers diagnosed with the major smoking-related comorbidities, such as acute myocardial infarction, in order to develop specific interventions and psychological support strategies.
Psychological distress related to smoking cessation in patients with acute myocardial infarction
Keywords: Myocardial infarction; Psychological; Smoking; Stress; Tobacco use cessation